Exploring Sikh Traditions and Heritage - Singh, Pashaura (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Exploring Sikh Traditions and Heritage follows interdisciplinary approaches, namely, textual and historical analyses of Sikh texts and life-narratives of Guru Nanak to construct the critical events related to Babur's invasions of India; an examination of a non-Sikh text to understand the image of Guru Nanak in the Dadu-panthi tradition; following interview and ethnographic methods to critically look into the global politics behind the Kartarpur Corridor and the sacred heritage of the Darbar Sahib in Pakistan; understanding the nature of modern Sikh activism in both the US and the UK through rich ethnography and historical investigation; introducing a systematic analysis of autoethnography of a person's experience through reflexivity and connecting the personal story to the social, cultural, and political life, having synergy with Sikh sense-making process; and finally, sociological investigation into the changing nature of the Sikh institution of the Akal Takht. In addition to senior scholars, this volume initiates new researchers into the growing field of Sikh studies. It will be a useful resource for both scholars and students of Sikh studies, religion, medieval Indian history, and literature.